Predictive value of pressure reactive index and mean flow index in the prognosis of severe traumatic brain injury. - XIA, Jing; SHI, Yi; XU, Wei; HAN, Bing-sha; ZHANG, Ming; FENG, Guang (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
Objective To explore and evaluate the application value of pressure reactivity index (PRx) based on invasive intracranial pressure (ICP) and mean flow index (Mx) based on transcranial Doppler ultrasonography (TCD) noninvasive monitoring in severe traumatic brain injury (sTBI). Methods The clinical data of 64 patients with sTBI treated in He'nan Provincial People's Hospital from January 2024 to February 2025 were included. According to the Glasgow Outcome Scale (GOS), the patients were divided into the good prognosis (GOS score 3-5) group (n = 31) and the poor prognosis (GOS score 1-2) group (n = 33). All patients received ICP monitoring immediately after surgery for 3-7 d. The ICP-related indicators including average ICP, cerebral perfusion pressure (CPP) and PRx were collected, and the ICP dose with a threshold of 20 mm Hg (DICP20) was obtained. All patients were monitored by TCD with an interval of ≥ 3 d immediately after operation, and the specific value of Mx was obtained. Univariate and multivariate Logistic regression analyses were used to analyze of influencing factors for 6-month post-discharge prognostic outcomes in patients with sTBI. The receiver operating characteristic (ROC) curve was further drawn, and the area under the curve (AUC) was calculated to evaluate the ability of each parameter to predict poor prognosis. Pearson correlation analysis was used to further analyze the correlation between PRx and Mx. Results Logistic regression analysis showed that higher ICP (OR = 2.439, 95%CI: 1.077-5.526; P = 0.033), higher PRx (OR = 14.932, 95%CI: 2.215-100.666; P = 0.005) and higher Mx (OR = 3.087, 95%CI: 1.145-8.324; P = 0.026) were risk factors for 6-month post-discharge prognostic outcomes in patients with sTBI. The AUC of ICP, PRx and Mx was 0.912 (95%CI: 0.814-0.968, P = 0.033), 0.958 (95%CI: 0.876-0.992, P = 0.005) and 0.859 (95%CI: 0.749-0.933, P = 0.026), and the prediction efficiency of the three was the same (Z = 0.850, P = 0.396; Z = 1.128, P = 0.259; Z = 1.856, P = 0.063). Pearson correlation analysis showed that the overall correlation between the mean values of all records of PRx and Mx was moderate (r = 0.521, P = 0.000). Conclusions ICP, PRx and Mx were the risk factors for 6-month post-discharge prognostic outcomes in patients with sTBI. Mx can be used as a noninvasive way to evaluate the cerebral autoregulation (CA) function of patients with sTBI, and has a certain predictive ability for the prognosis. There was a moderate correlation between PRx and Mx, suggesting that they provide different information of CA function.